Hepatobiliary and pancreatic manifestations in inflammatory bowel disease: an umbrella review of meta-analyses - Runsheng Hong; Zhixue Li; Meng Li; Yun Dai (Therapeutic Advances in Gastroenterology)
Background: Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), can affect the hepatobiliary system and pancreas, substantially impacting the life quality of patients. Objectives: To evaluate the quality of evidence and comprehensively assess the validity of associations of IBD with hepatobiliary and pancreatic diseases. Design: We performed an umbrella review of existing meta-analyses in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) recommendations. Data sources and methods: We systematically searched PubMed, Embase, and Web of Science from inception to April 2024, to identify and appraise meta-analyses examining IBD and risk of hepatobiliary and pancreatic manifestations. Methodologic quality was assessed with A Measurement Tool to Assess Systematic Reviews (AMSTAR 2) and the strength of evidence was graded according to prespecified criteria. Results: A total of 14 meta-analyses of observational studies were included. The strongest-validity evidence suggested the significant associations between IBD and risk of gallstones (odds ratio (OR) = 1.72; 95% confidence interval (CI) = 1.40–2.12) and acute pancreatitis (OR = 3.11; 95% CI = 2.93–3.30). Highly suggestive evidence indicated a significantly increased risk of hepatobiliary cancer in UC (incidence rate ratio (IRR) = 2.05; 95% CI = 1.52–2.76) and CD (IRR = 2.31; 95% CI = 1.25–4.28). In addition, highly suggestive evidence indicated that IBD was associated with portal venous system thrombosis. Suggestive evidence showed a significantly higher prevalence of primary sclerosing cholangitis, non-alcoholic fatty liver disease, autoimmune hepatitis, and autoimmune pancreatitis in IBD patients than in the general population. Conclusion: The associations between IBD and multiple hepatobiliary and pancreatic disorders showed varying levels of evidence and magnitude of risk. Further high-quality primary studies are needed to identify IBD patients who are more at risk and would benefit the most from screening and prevention programs. Trial registration (PROSPERO): CRD42023451461.